2011
DOI: 10.1002/mc.21846
|View full text |Cite
|
Sign up to set email alerts
|

Combined histone deacetylase and cyclooxygenase inhibition achieves enhanced antiangiogenic effects in lung cancer cells

Abstract: PGE2 is an important pro-angiogenic and pro-proliferative cytokine and the key enzymes modulating its levels, COX-2 and 15-PGDH play important opposing roles in carcinogenesis. Previously we found loss of 15-PGDH expression in lung cancer and its reactivation leads to strong in vivo tumor-suppressive effect via an antiangiogenic mechanism. Here we find that HDAC inhibitors (HDACI), such as trichostatin A (TSA) and vorinostat could reactivate 15-PGDH expression but overall induce PGE2 generation and this is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…As a consequence, class I HDAC inhibition could induce the transcriptional activation of NF-kB-driven genes. Consistently, a significant COX-2 induction was recently showed in lung cancer cells following trichostatin A or SAHA treatment [27]. Here, we showed, for the first time, that the class I HDAC chemical inhibitor MS-275 and selective silencing of both HDAC1 and HDAC3 are able to induce the transcription of COX-2 gene and the accumulation of the functional enzyme independently of the KRAS status.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As a consequence, class I HDAC inhibition could induce the transcriptional activation of NF-kB-driven genes. Consistently, a significant COX-2 induction was recently showed in lung cancer cells following trichostatin A or SAHA treatment [27]. Here, we showed, for the first time, that the class I HDAC chemical inhibitor MS-275 and selective silencing of both HDAC1 and HDAC3 are able to induce the transcription of COX-2 gene and the accumulation of the functional enzyme independently of the KRAS status.…”
Section: Discussionsupporting
confidence: 83%
“…For example, a recent study demonstrated that pan-HDAC inhibitors induce cyclooxygenase-2 (COX-2) expression in lung cancer cells, leading to a stimulation of endothelial cell proliferation [27]. Since COX-2 has been also associated to pancreatic cancer cell proliferation [28] or tumor growth [29][31], we hypothesized that COX-2 overexpression may also be induced in PDAC when treated with HDAC inhibitors, leading to reduced efficiency and hence therapeutic failure.…”
Section: Introductionmentioning
confidence: 99%
“…While dual-acting compounds comprising NSAIDs and other agents exist 20 , none contain HDACi and NSAIDs combined as a single component. Moreover, results from in vitro studies suggest that enhanced cytotoxic effect could be achieved by combining NSAIDs and HDACi in cancer cell lines 21 . In this study, we designed and synthesized bifunctional compounds with HDAC and COX-2 inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%
“…In our studies, we tried to find whether COX-2 is regulated by IGFBP-4 in lung cancer inflammatory microenvironment by the addition of LPS to the cell media. COX-2 inhibition suppressed cell proliferation and improved antiangiogenic and apoptotic effects in lung cancer (Qiu et al, 2012;Wang et al, 2013). IGFBP-4 neutralizing antibody treatment could increase LPSinduced COX-2 protein expression in lung cancer cells.…”
Section: Discussionmentioning
confidence: 94%
“…COX-2 as an inflammatory mediator promotes cell growth, migration, invasion, and tumor progression to metastasis (Liu et al, 2001;Larkins et al, 2006;Hu et al, 2009;Lyons et al, 2011;Karavitis et al, 2012). COX-2 inhibition suppressed cell proliferation and improved antiangiogenic and apoptotic effects in lung cancer (Qiu et al, 2012;Wang et al, 2013). In addition, IGFBP-4 was downregulated and COX-2 was upregulated in lung cancer tissue compared to matched adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%